Facile regioselective decomposition of tosylhydrazones: an application towards the synthesis of alpha-lipoic acid - Chavan, Subhash P.; Kale, R. R.; Pasupathy, K. (Synlett, 2005)
A facile regioselective decomposition of tosylhydrazones using NaOH as a base in refluxing isopropyl alcohol is described. This finding has been Successfully applied towards the synthesis of (&PLUSMN;)-α-lipoic acid (1).
Keywords: alpha-lipoic acid; Olefins; Regioselectivity; tosylhydrazones

First asymmetric total synthesis of penarolide sulfate A(1) - Mohapatra, Debendra K.; Bhattasali, Debabrata; Gujar, Mukund K.; Khan, Mohammad Islam; Shashidhara, K. S. (European Journal of Organic Chemistry, 2008)
Penarolide sulfate A(1), with three contiguous stereogenic centers on a macrocyclic skeleton, affords promise as an alpha-glucosidase inhibitor. Herein, we describe the first asymmetric total synthesis of this natural product. A stereoselective strategy for rapid assembly of the complete framework of the 30-membered macrocyclic core is delineated herein. Sequential amidation and intramolecular Sonogashira cross-coupling reactions were pivotal to the success of our efforts. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Asymmetric synthesis; C-C coupling; Dihydroxylation; epoxidation; Macrocycles; Regioselectivity; Total synthesis

Regioselective O-acylation of myo-inositol 1,3,5-orthoesters: dependence of regioselectivity on the stoichiometry of the base - Sureshan, Kana M.; Devaraj, Subramanian; Shashidhar, Mysore S. (Tetrahedron, 2009)
A metal mediated unusual 1-3 acyl migration from C4-O to C2-OH of myo-inositol 1,3,5-orthoformate was observed during the alkylation of racemic 4-O-benzoyl-myo-inositol 1,3,5-orthoformate. This has been exploited for the selective esterification of either the C4(6)-OH or the C2-OH of myo-inositol by varying the amount of the base used. While the use of 1 equiv of the base (sodium hydride or potassium tert-butoxide) for the acylation of myo-inositol orthoesters gives the corresponding C4-ester exclusively, the use of two or more equivalents of base for the same reaction gives the C2-ester exclusively. The relatively higher stability of the alkoxide of racemic 2-O-acyl-myo-inositol 1,3,5-orthoester as compared to the alkoxide of 4-O-acyl-myo-inositol 1,3,5-orthoester is suggested to be responsible for the observed isomerization. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Cyclitol; Inositol; Orthoester; Regioselectivity; transesterification

Tethered aminohydroxylation route to L-arabino-[2R,3S,4R] and L-xylo-[2R,3S,4S]-C-18-phytosphingosines - Dubey, Abhishek; Kumar, Pradeep (Tetrahedron Letters, 2009)
A concise and highly efficient synthesis of L-arabino-[2R,3S,4R] and L-xylo-[ 2R,3S,4S]-C-18-phytosphingosines has been achieved. The synthetic strategy features the Sharpless kinetic resolution and tethered aminohydroxylation as the key steps. (C) 2009 Elsevier Ltd, All rights reserved.
Keywords: Phytosphingosine; Regioselectivity; Sharpless asymmetric kinetic resolution; Sphingolipids; stereoselectivity; Tethered aminohydroxylation

Orthogonally protected cyclohexanehexols by a ``one reaction - one product'' approach: efficient access to cyclitols and their analogs - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
Differentially protected myo-inositol derivatives were prepared from commercially available myo-inositol through regioselective O-alkylation reactions, which give a single product in each step. These derivatives were converted into six isomeric inositol derivatives carrying orthogonal hydroxy protecting groups. For all these reactions, conditions were chosen to prevent the formation of isomeric products, which obviates the need for separation of isomers and provides the required cyclitol derivative in very good yields. The synthetic potential of these derivatives was illustrated by the conversion of some of the orthogonally protected inositol derivatives into other cyclitol derivatives. Isomeric inositols were also prepared by the global deprotection of all the hydroxy groups.
Keywords: Alkylation; cyclitols; Inositol; Protecting groups; Regioselectivity

Modular synthesis of dihydroxyacetone monoalkyl ethers and isosteric 1-hydroxy-2-alkanones - Gueclue, Deniz; Rale, Madhura; Fessner, Wolf-Dieter (European Journal of Organic Chemistry, 2015)
Straightforward methods for the efficient, systematic preparation of libraries of the title compound classes have been evaluated. A general and efficient modular route to dihydroxyacetone monoethers was developed based on trityl glycidol, which, through epoxide opening, oxidation, and deprotection, provided variously alkylated ethers by three routine operations in good overall yields (eight examples, 24-59%). The preparation of structurally related 1-hydroxyalkanones depends on the availability of the most economic starting materials and on their physicochemical properties. Thus, the most practical one-step approaches consisted of the sec-selective oxidation of short-chain 1,2-diols (<= C-6) using NaOCl, and the direct ketohydroxylation of 1-alkenes (>= C-6) using buffered stoichiometric KMnO4 or catalytic RuO4 with reoxidation by oxone, for which mostly good overall yields were achieved on a multigram scale (nine examples, 15-78%).
Keywords: Alkylation; Hydroxylation; Ketones; Oxidation; Oxygenation; Regioselectivity; synthetic methods

Synthesis of yangjinhualine A - Deore, Prashant S.; Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2015)
Selective reduction of 3-(4-hydroxyphenyl)-2-methylmaleic anhydride provides access the corresponding gamma-hydroxybutenolide natural product yangjinhualine A.
Keywords: anhydrides; lactones; Natural products; reduction; Regioselectivity

Pd-catalyzed regioselective mono-arylation: quinazolinone as the inherent directing group for C(sp(2))-H activation - Garad, Dnyaneshwar N.; Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2017)
The Pd-catalyzed quinazolinone-directed regioselective monoarylation of aromatic rings by C-H bond activation is developed. A broad substrate scope is demonstrated for both quinazolinone as well as diary-liodonium triflates. The use of a base was found to be crucial for this transformation, unlike for the known nitrogen-directed arylations. All of the novel quinazolinones of biological interest were synthesized by using the operationally simple Pd(II)-catalyzed arylation reaction.
Keywords: Aromatic rings; catalysis; Chemical activation; Chemical reactions; Palladium compounds; Regioselectivity

Photoinduced multicomponent regioselective synthesis of 1,4,5-trisubstituted-1,2,3-triazoles: transition metal-, azide- and oxidant-free protocol - Sai Allaka, Bhargava; Basavoju, Srinivas; Rama Krishna, Gamidi (Advanced Synthesis & Catalysis, 2021)
A transition metal- and azide-free approach is explored to synthesize 1,4,5-trisubstituted-1,2,3-triazoles under sunlight. The reaction proceeds via C-N and N-N bond formations. These regioselective 1,2,3-triazoles are obtained from isatin Schiff bases, benzaldehydes and tosylhydrazine in the presence of base. This protocol offers the structurally diverse 1,2,3-triazole derivatives with 75-90% yields.
Keywords: 1; 2; 3-triazoles; 4; 5-trisubstituted-1; azide- and oxidant free protocol; Cycloaddition; milder reaction conditions; molecular diversity; Multicomponent reaction; Regioselectivity; transition metal-

Regioselectivity in metalloradical catalyzed C-H bond activation: a theoretical study - Mukherjee, Anirban; Singh, Ritesh; Mane, Kishor D.; Das, Gourab Kanti (Journal of Organometallic Chemistry, 2022)
Pure quantum mechanical calculations were performed to find out the origin of regioselectivity under the metalloradical catalysis (MRC) by Co(II)-porphyrin, which showed regioselectivity is the inherent property of the aminyl radical generated from the sulfamoyl azide substrate. Different conformational analysis for the transition state from alpha-Co-III-aminyl radical to zeta-Co-III-alkyl radical formation have been studied to find out the most stable conformation for the preferable selectivity. The outcome of our study completely agrees with the reported experimental results. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: C-H activation; DFT; Metalloporphyrin; Metalloradical; Regioselectivity

Transition metal- and oxidant-free regioselective synthesis of 3,4,5-trisubstituted pyrazoles by means of [3+2] cycloaddition reactions - Allaka, Bhargava Sai; Basavoju, Srinivas; Gamidi, Rama Krishna (ChemistrySelect, 2022)
A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal- and oxidant-free, three component [3+2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through C-C and C-N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.
Keywords: 3; 4; 5-trisubstituted pyrazoles; Cycloaddition; Multicomponent reaction; Oxidant free; Regioselectivity; Transition metal free

Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity

Structure of epoxide hydrolase 2 from Mangifera indica throws light on the substrate specificity determinants of plant epoxide hydrolases - Bhoite, Ashwini; Gaur, Neeraj K.; Palange, Megha; Kontham, Ravindar; Gupta, Vidya; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2024)
Epoxide hydrolases (EHs) are a group of ubiquitous enzymes that catalyze hydrolysis of chemically reactive epoxides to yield corresponding dihydrodiols. Despite extensive studies on EHs from different clades, generic rules governing their substrate specificity determinants have remained elusive. Here, we present structural, biochemical and molecular dynamics simulation studies on MiEH2, a plant epoxide hydrolase from Mangifera indica. Comparative structure-function analysis of nine homologs of MiEH2, which include a few AlphaFold structural models, show that the two conserved tyrosines (MiEH2Y152 and MiEH2Y232) from the lid domain dissect substrate binding tunnel into two halves, forming substrate-binding-pocket one (BP1) and two (BP2). This compartmentalization offers diverse binding modes to their substrates, as exemplified by the binding of smaller aromatic substrates, such as styrene oxide (SO). Docking and molecular dynamics simulations reveal that the linear epoxy fatty acid substrates predominantly occupy BP1, while the aromatic substrates can bind to either BP1 or BP2. Furthermore, SO preferentially binds to BP2, by stacking against catalytically important histidine (MiEH2H297) with the conserved lid tyrosines engaging its epoxide oxygen. Residue (MiEH2L263) next to the catalytic aspartate (MiEH2D262) modulates substrate binding modes. Thus, the divergent binding modes correlate with the differential affinities of the EHs for their substrates. Furthermore, long-range dynamical coupling between the lid and core domains critically influences substrate enantioselectivity in plant EHs.
Keywords: Enantioselectivity; Epoxide hydrolase; molecular dynamics simulation; Regioselectivity; X-ray crystallography

Regioselective difluoroalkylation of 2-pyridones with fluoroalkyl bromides enabled by a nickel(II) catalyst - Pradhan, Chandini; Khandelwal, Disha; Punji, Benudhar (Chemistry-An Asian Journal, 2025)
Regioselective C-H difluoroalkylation of diverse 2-pyridones with ethyl bromodifluoroacetates and bromodifluoroacetamides is accomplished by using a (dppf)NiCl2 catalyst under mild conditions. This efficient protocol could deliver a variety of C-3 difluoroalkylated pyridones with the tolerance of a range of highly susceptible functionalities, such as -Cl, -Br, -I, -COMe, -CN, -NMe2 and -NO2, including heteroarenes like pyridinyl, furanyl, thiophenyl and carbazolyl moieties. A preliminary mechanistic study suggests the radical pathway for the reaction involving fluoroalkyl radical intermediate.
Keywords: 2-pyridones; Difluoroalkylation; Nickel; radical intermediate; Regioselectivity